Kapitał społeczny a regionalne strategie innowacji - Salus, Aneta (Social Capital vs. Regional Innovation Strategies, 2009)
In the times of globalization, technical and technological advancement, as well as information society, it is unavoidable to perform transformations directed towards knowledge based economy. Investments in innovations, research or workers' skills and their influence on economic growth at the level of regions have become more and more important, and such development turns out to be the key objective for enhancing mechanisms supporting the implementation of innovations. Therefore, it occurs the need to prepare documents regulating and supporting the activities of regional or local level's authorities in defining and introducing an effective system of backing up both innovations and competitiveness. This function is to be performed by Regional Innovation Strategies. It is beyond any doubt, that the above-mentioned documents include goals and assumptions prepared with all due care and involvement, but do they cover all factors crucial for their effective implementation? The answer to this question is of great importance, since it points to real success perspectives. The article is an attempt to provide an answer to the above question. The paper indicates the need to take into consideration the level of social capital at every stage while creating regional innovation strategies. Such capital, according to the author, determines the speed, methods, tools and efficiency as well as effectiveness of the mentioned strategies implementation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 46, s. 119-125